Problematika Ratifikasi Konvensi Konvensi Organisasi Perburuhan Internasional (ILO) C188 Sebagai Perlindungan Hukum Bagi Pekerja Migran Indonesia - Suharnata, Suko; Shahrullah, Rina Shahriyani; Nurlaily, Nurlaily (Jurnal Selat, 2023)
Indonesian Migrant Workers (PMI) who work in the domestic sector generally have received a lot of attention and attention from the public, as crew members of fishing boats owned by foreign companies receive less attention both regarding safety and the protection of their rights. Therefore, this research aims to emphasize the importance of Indonesia to ratify the convention as a form of effort to provide protection for workers on foreign ships, as well as provide a sense of security and legal certainty in the future. The Indonesian government has not taken serious steps to accommodate the interests of Indonesian crew members working on foreign fishing vessels. The research used in this research is juridical-normative legal research. The state has an obligation to provide human rights protection without having to be asked. Therefore, it is important for the Indonesian government to ratify ILO Convention 188 of 2007 in overcoming legal replacements left by national regulations, guaranteeing workers' rights, and creating legal certainty. The need for harmonization of existing and applicable laws and regulations regarding the protection of fishery workers in Indonesia should be taken into consideration when the government decides to ratify ILO Convention 188 of 2007.